2010
DOI: 10.1152/physiolgenomics.00013.2010
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling in response to adiponectin in human cancer-derived cells

Abstract: The adipocyte-derived hormone adiponectin exerts protective actions in several disorders, including some cancers. However, while growing data suggest that adiponectin could be an effective anticancer agent, its mechanism of action in cancer cells is still poorly known. Here, using microarrays, we identified a set of 1,301 genes commonly modulated in three cancer-derived cell lines in response to short-term stimulation with full-length recombinant human adiponectin. Most of these genes are involved in translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Our studies for profile-2 genes (Table 4) revealed the cell cycle control proteins, and Aryl hydrocarbon receptor, and ATM pathways with the highest number of gene hits. Of interest is the ATM pathway (Additional file 1: Figure S5D) which phosphorylates several proteins to activate the DNA damage checkpoint, leading to cell cycle arrest, apoptosis and cell differentiation [59]. This pathway also regulates DNAPK which has been associated with bone marrow failure [60].…”
Section: Resultsmentioning
confidence: 99%
“…Our studies for profile-2 genes (Table 4) revealed the cell cycle control proteins, and Aryl hydrocarbon receptor, and ATM pathways with the highest number of gene hits. Of interest is the ATM pathway (Additional file 1: Figure S5D) which phosphorylates several proteins to activate the DNA damage checkpoint, leading to cell cycle arrest, apoptosis and cell differentiation [59]. This pathway also regulates DNAPK which has been associated with bone marrow failure [60].…”
Section: Resultsmentioning
confidence: 99%
“…The sets of genes expressed in human normal liver, HCC and HepG2 cells were obtained from previous published studies (Supporting information, Table S1). Intracellular pathways or transcription factors modulated by various stimuli, were identified and retrieved from previously published experiments performed on different human cancer cell lines, and HepG2 cells (Supporting information, Table S2 and [16]).…”
Section: Discussionmentioning
confidence: 99%
“…Table S4. Sets of human genes retrieved from published global gene analyses (According to the procedure previously described [16]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations